RT essentials - Vincent, Jesse (O'Reilly, 2005)
In a typical organization, there's always plenty that to do such as: pay vendors, invoice customers, answer customer inquiries, and fix bugs in hardware or software. You need to know who wants what and keep track of what is left to do. This is where a ticketing system comes in. A ticketing system allows you to check the status of various tasks: when they were requested, who requested them and why, when they were completed, and more. RT is a high-level, open source ticketing system efficiently enabling a group of people to manage tasks, issues, and requests submitted by a communi.